About the official alphabets of Quechua and Aymara - Zúñiga C., Madeleine (1987)
Since the historic episode in which the Inca Atahualpa threw the Bible that Father Valverde would offer him, writing was a mystery for the Quechua people and took on a very special meaning for them. The written language that "speaks" to those who know how to read it was one more element of their age-old oppression. Since access to writing was denied, the monolingual Quechua-speaker also believed that only Spanish possessed this unattainable power. However, from the first decades of the Colony, the chroniclers and missionaries wrote Quechua in their reports, stories and religious books; in doing so, logically, they tried to reproduce what they heard with the only instrument they handled, the Spanish alphabet of the time, which was still in the process of being formed.